KONSEP PENDIDIKAN AGAMA ISLAM BERBASIS ISLAM TERPADU ANALISIS TERHADAP ISI KURIKULUM SDIT BIAS INDONESIA TAHUN 2018 - Rz. Ricky Satria Wiranata (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Islamic Religious Education is accused of shackling the development of Science and Technology. The practice of dichotomy and secularization between General Sciences and Islamic Sciences resulted in the inability of Muslims to integrate knowledge integrally. There have actually been many attempts by practitioners of Islamic Religious Education to integrate them, but they have not yet found a final formulation (ongoing process), especially at the philosophical level. One of the Islamic Religious Education Institutions that has the spirit of integrating integral ideas is SDIT BIAS Indonesia which was born in 1994 and became the pioneer of Integrated Islamic Religious Education in Yogyakarta. On this basis, researchers are interested in formulating philosophical ideas in the form of a concept map based on the SDIT BIAS Indonesia Integrated Curriculum. The results of this study are a review and critical analysis of the philosophical concepts contained in the 2018 BIAS Indonesia SD curriculum.